Microbial boundaries in peri-implantitis: a review of pathogen-related advances - Ehab Qasim Talib; Ghada Ibrahim Taha; Dhuha Mahmood Ali; Sahar Hashim Al-Hindawi; Fadia Abd Almuhsin Al-Khayat; Israa Amer Hasan (Folia Medica)
In the field of implantology, peri-implantitis is still a common complication of implant failure. Similar to periodontal disease, this kind of pathological condition is characterized by inflammation of the tissues surrounding dental implants or fillings. The sources of infection have been shown to be chronic periodontitis and poor maintenance of the communion. A thorough examination of the intricate components of peri-implantitis was sought in this review in order to identify common characteristics of the disease with regard to bacteria, biofilm formation, host immunological responses, diagnostic tools, and therapeutic treatments. The aim of this study was to provide a detailed overview of the different bacterial species associated with peri-implantitis, a clinical condition similar to periodontitis, characterized by a higher prevalence of staphylococci and enteric bacteria. The study underscores the importance of employing sophisticated diagnostic methods like cone beam computed tomography. It covers a range of therapeutic approaches including surgical and non-surgical techniques as well as strategies stressing host-modification and photodynamic treatment. The study was conducted using pertinent publications from scientific databases, including Scopus, Google Scholar, PubMed, and Web of Science. We searched these databases using the following terms: periodontitis, microbial, dental implants, peri-implantitis, and biofilm formation.